1995
DOI: 10.1126/science.7537388
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Memory B Cells and Plasma Cells in Vitro

Abstract: After germinal center B cells undergo somatic mutation and antigen selection, they become either memory B cells or plasma cells, but the signal requirements that control entry into either pathway have been unclear. When purified human germinal center cells were cultured with interleukin-2, interleukin-10, and cells expressing CD40 ligand, cells with characteristics of memory B cells were generated. Removal of CD40 ligand from the system resulted in terminal differentiation of germinal center B cells into cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
365
1
5

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 534 publications
(396 citation statements)
references
References 30 publications
22
365
1
5
Order By: Relevance
“…In these studies, plasma cells were identified as cells containing intracellular Ig, increased expression of CD38, and concomitant down-regulation of CD20, consistent with the morphology and phenotype of plasma cells present in human bone marrow (20,21). After initial stimulation of GC or memory B cells with CD40 ligand (CD40L), IL-2, and IL-10, a greater proportion of plasma cells was generated when these activated cells were recultured in the absence of CD40L (17)(18)(19). These findings suggested that CD40L interrupted plasma cell development while concomitantly promoting expansion of nondifferentiated B cell blasts (17)(18)(19).…”
supporting
confidence: 61%
See 3 more Smart Citations
“…In these studies, plasma cells were identified as cells containing intracellular Ig, increased expression of CD38, and concomitant down-regulation of CD20, consistent with the morphology and phenotype of plasma cells present in human bone marrow (20,21). After initial stimulation of GC or memory B cells with CD40 ligand (CD40L), IL-2, and IL-10, a greater proportion of plasma cells was generated when these activated cells were recultured in the absence of CD40L (17)(18)(19). These findings suggested that CD40L interrupted plasma cell development while concomitantly promoting expansion of nondifferentiated B cell blasts (17)(18)(19).…”
supporting
confidence: 61%
“…For reculture experiments, B cells were cultured for 4 days with CD40L, IL-2, and IL-10, harvested, and washed thoroughly with PBS. The cells were recultured with IL-2 and IL-10 in the absence or presence of CD40L for an additional 4 days (17). A known number of CaliBRITE beads (BD Biosciences) were added to culture wells before harvesting, and the number of viable B cells in each culture condition was calculated as a function of the ratio of beads to live cells (24,26,27).…”
Section: Cfse Labeling and B Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, factors that are responsible for this rapid cell division have not been identified. Many cytokines have been reported to augment human GC-B cell proliferation in vitro, one of the most potent being IL-2 (6,73). In the absence of IL-2, GC-B cell recovery has been shown to be decreased by at least 3-fold (6).…”
Section: Discussionmentioning
confidence: 99%